Diffusion tensor imaging of visual pathways in patients with acute and chronic optic neuritis - Ahmet Onur Keskin (Guoji Yanke Zazhi, 2018)
AIM: To investigate diffusion tensor imaging(DTI)evaluations of visual pathways in patients with acute and chronic optic neuritis(ON), and investigate the correlations between visual disability, retinal nerve fiber layer thickness(RNFLT)and diffusion index changes. METHODS: We performed DTI in 26 patients and 13 healthy controls. Patients had acute ON in 17 eyes, chronic ON in 20 eyes and 15 unaffected eyes. In all participants, the visual afferent system was evaluated with neuro-ophthalmological examinations, optical coherence tomography(OCT), visual evoked potential(VEP), orbital and cranial MRI. RESULTS: Fractional anisotropy(FA)in the optic nerves was lower in patients with acute ON and chronic ON than controls(P=0.28). Mean diffusivity(MD)in the optic nerves was higher in patients with acute and chronic ON than the unaffected eyes of patients and controls(P<0.01). Retinal nerve fiber layer thickness, P100 amplitude and latency and visual acuity(VA)were significantly different between patient and control groups(P<0.01). Optic chiasm MD values were higher in the patient group compared to the control group(P=0.011). FA and MD measured in the optic tracts significantly were different between groups(P=0.032, P=0.013, respectively). In the correlation analysis, fractional anisotropy in the optic nerves was correlated with P100 latency in acute ON(P=0.021). Mean diffusivity was correlated with RNFLT, visual acuity and P100 latency(P<0.05). Fractional anisotropy was correlated with mean diffusivity and visual acuity, and, mean diffusivity was correlated with P100 amplitude and RNLF thickness in chronic ON(P<0.05). Reduction in visual acuity was correlated with increase in mean diffusivity and decrease in fractional anisotropy(P<0.05). CONCLUSION: DTI can demonstrate abnormalities in a tissue that appears normal in orbital MRI. Our results suggested that DTI derived measurements correlate with visual disability and tissue injury and therefore they are important from a clinical point of view and also in understanding the pathological processes.